Analisis Sistem Penggalangan Dana Sosial di Panti Asuhan Yatim Muhammadiyah Slawi - Wahyu Prasetyawati, Aries Setyani; Faizin, Muhammad Yusril (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study discusses the social fundraising system implemented at the Muhammadiyah Slawi Orphanage. The fundraising process is still conventional, involving direct donations to the treasurer and manual recording using Microsoft Excel. The main problem faced by the institution is the lack of digital technology utilization to improve transparency, effectiveness, and outreach. The research methods used include observation, interviews, and literature review. The system analysis was conducted using a SWOT (Strength, Weakness, Opportunity, Threat) approach. The results show that the current system has the advantage of high donor trust and public support, but its main weakness lies in the limited transparency of digital reports and publications. The main opportunity lies in the use of a website-based online donation system that can expand donor reach and improve accountability. The recommendation of this study is the development of a web-based fundraising information system integrated with an automated reporting system to support transparency, effectiveness, and sustainability of the social institution's operations. Keywords: Donors, Digitalization, Fundraising, Orphanage, SWOT, Transparency